Chemical thinning of peach trees - de Mello Farias , Roseli; Farias Barreto, Caroline; Martins, Carlos Roberto; Zandoná, Renan Ricardo; Vighi Schiavon , Andressa; de Mello Farias , Paulo Celso (Comunicata Scientiae, 2022)
Peach tree thinning is essential to harvest quality fruits and to keep balanced production for several years. Manual thinning of peach trees demands much work force and increases production costs. Chemical thinning may be an alternative solution, but efficiency depends on doses and species. This study aimed at evaluating the effect of metamitron – applied at different concentrations – on chemical thinning of peach trees in the south of Brazil. The experiment was carried out in a commercial peach tree orchard where ‘Sensação’ cultivars, in Morro Redondo, Rio Grande do Sul (RS) state, Brazil. The following metamitron concentrations were applied at concentrations of 100 mg L-1, 200 mg L-1, 300 mg L-1, 400 mg L-1, manual thinning was carried out 40 days after full bloom (DAFB) and to the treatment where the plants have no thinning. Fruit abscission, effective fructification, total number of plants per plant, production per plant, mean mass and fruit diameter were evaluated. Concentrations of 300 and 400 mg L-1 metamitron 40 DAFB provides promoted high fruit abscission, besides decreasing the number of fruits and production. Therefore, concentrations of 100 and 200 mg L-1 of metamitron 40 DAFB provides results in an efficient thinning practice similar to manual thinning for production, mass and fruit diameter.